2000
DOI: 10.1002/(sici)1099-0488(20000315)38:6<889::aid-polb9>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

NMR investigations into heterogeneous structures of thermosensitive microgel particles

Abstract: The internal properties of submicron poly(N‐isopropylmethacrylamide) latex particles were investigated as a function of the methylene bisacrylamide (MBA) concentration used as a crosslinker. Two experimental approaches were performed. First, quasi‐electric light scattering measurements provided the size variation of the particles as a function of temperature, from which the swelling capacity of the particles as a function of MBA were estimated. In addition, the broadening and lowering effects of the volume pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 22 publications
8
104
1
1
Order By: Relevance
“…The difference could be rationalized by assuming a constant solvent self-diffusion coefficient in the core of the particles regardless of temperature, suggesting that the particle cores of microgels are consistently more dense than the outer shells. Guillermo et al confirmed this observation using transverse proton relaxation measurements to discriminate different structural components within microgels, identifying a general decrease in chain density from the core to the outer shell of the PNIPAM microgel [72]. Thus, the general SANS chain density observations regarding microgel structure can be confirmed using NMR techniques.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 76%
“…The difference could be rationalized by assuming a constant solvent self-diffusion coefficient in the core of the particles regardless of temperature, suggesting that the particle cores of microgels are consistently more dense than the outer shells. Guillermo et al confirmed this observation using transverse proton relaxation measurements to discriminate different structural components within microgels, identifying a general decrease in chain density from the core to the outer shell of the PNIPAM microgel [72]. Thus, the general SANS chain density observations regarding microgel structure can be confirmed using NMR techniques.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 76%
“…[13][14][15][16] The structural inhomogeneities inside microgel particles consisting of poly( N -isopropylmethacrylamide) (PNIPMAAm) were studied using 1 H NMR transverse relaxation measurements. [ 17 ] Different structural regions were distinguished by their different proton mobilities detected. The internal particle morphology was detected to be heterogeneous.…”
Section: Dynamic Light Scattering (Dls)mentioning
confidence: 99%
“…The fi ts with two exponential functions [ Equation(17) ] are shown by solid lines and have χ 2 ≈ 0.0011 and correlation coeffi cients of R 2 ≈ 0.9911.…”
mentioning
confidence: 99%
“…Light scattering [6,7], neutron scattering [8,9], and NMR [10] analysis are the only methods which can practically be used to give some independent insight into the morphological changes occurring in [11]. b Calculated from isothermal titration calorimetry [11].…”
Section: Introductionmentioning
confidence: 99%